2011
DOI: 10.1002/hed.21720
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of acute and chronic comorbidity in patients with squamous cell carcinoma of the head and neck

Abstract: High rates of acute and chronic comorbidity were observed; knowledge of comorbidity burden aids in establishing a benefit-risk profile for investigational SCCHN therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
4
28
1
Order By: Relevance
“…The data presented herein further support results from our previous studies in UADT malignancies regarding an association between metformin use and improved survival outcomes . It is important to note that, although the prevalence of diabetes in the HNSCC population at large is estimated to be <10%, our cohort presented with 20% of patients carrying a diagnosis of diabetes mellitus at the time of cancer treatment …”
Section: Discussionsupporting
confidence: 88%
“…The data presented herein further support results from our previous studies in UADT malignancies regarding an association between metformin use and improved survival outcomes . It is important to note that, although the prevalence of diabetes in the HNSCC population at large is estimated to be <10%, our cohort presented with 20% of patients carrying a diagnosis of diabetes mellitus at the time of cancer treatment …”
Section: Discussionsupporting
confidence: 88%
“…28 The consequent barriers to health care access experienced in this population may explain the higher prevalence of severe comorbidity and multiple different conditions observed in our population compared to others. 4, 5, 7 ,…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated the increased prevalence of comorbidity in head and neck cancer patients, 2, 4, 5 which can impact treatment selection 6, 7 and prognosis. 813 For example, patients with severe cardiovascular or respiratory comorbidity may be excluded from surgical treatment because of an increased potential for adverse treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that the presence of two or more patient comorbidities was a significant risk factor for NCM. This may reflect the fact that the HNC patients have a higher prevalence of comorbidities than the general population (Landis et al., ) and that cancer patients with severe comorbidities have a higher incidence of complications and mortality secondary to cancer treatment (Derks, de Leeuw & Hordijk, ; Ferrier, Spuesens, Le Cessie & Baatenburg de Jong, ). Indeed, the cancer treatment itself may increase the risk of comorbidities even after 1 year of treatment, particularly in patients undergoing chemotherapy (Montero‐Miranda & Ganly, ).…”
Section: Discussionmentioning
confidence: 99%